Recreational mathematics and the mathematical logical thought development in students of Unheval National High School from Huánuco - Camara Acero, Andres A. (2017)
This work had as aim to determine influence of the application of the recreational mathematic in the mathematicial logical thought development in students from national high school of Hermilio Valdizan University, starts with the question What way, The search was experimental with transactionalortransversalstudieswhichadressedtoexplainhowrecreationalmathematics makes easy the mathematicial logical thought development in students of this educational center with a quasi experimental design with application of pre test and post test, having an experimental group, obtaining as a result that in the “good” category that represents scores from 13 to 16, are 53,85%. Therefore the recreational mathematics application optimized the mathematical logical thought development and improved the logical reasoning about study; Concluding the utilization of the recreational mathematics in students from this school, help mathematicallogical thought development,showing positive and growth indicators in the experimental group with respect to control group and the academic performances in students of the experimental group with the Recreational Mathematics, in comparison to the academic performance of the students of control group, they have a significantly positive growth, which shows students are interested in Matematics learning.